Plans and Interventions of South African Grade 1 Educators During the 2020 Lockdown Period - Annemie Grobler (Research in Social Sciences and Technology, 2021)
The extended lockdown in 2020 found South African educators employing innovative strategies to teach and assess Foundation Phase learners. Educators had to make do with reduced hours in the classroom and experienced new challenges in delivering curriculum content to learners that had barely grown accustomed to the formal classroom setup. Empirical research attempted to identify the plans and approaches used by grade 1 educators. The findings may indicate best practices as experienced in this time and help to inform the approach taken during future repetitions of extraordinary circumstances. A theoretical and conceptual framework based on the current constructivist approach adopted by the Curriculum Assessment and Policy Statement (CAPS) guided the empirical research and informed the construction of the questionnaire. The key findings were themed into strategies for presenting teaching and learning, communication, and the impact on schooling. Findings were compared to the premises of the theoretical framework and conclusions drawn. It was noted that educators were hesitant to move their schooling entirely to the virtual learning platform and eager to return to the school environment. Various obstacles posed by the digital divide were flagged as threats to future situations and the involvement of parents was emphasized. The resilience of educators to continue to ply their trade, and their belief in the indomitable spirit of children, may offer conducive circumstances for future innovations in education.